2011
DOI: 10.2147/opth.s21297
|View full text |Cite
|
Sign up to set email alerts
|

Changes in corneal biomechanics following different keratoplasty techniques

Abstract: Purpose:To evaluate corneal biomechanics with the Ocular Response Analyzer (ORA; Reichert Ophthalmic Instruments, Depew, NY) after penetrating keratoplasty (PK) and deep anterior lamellar keratoplasty (DALK).Subjects and methods:Sixty-three eyes of 63 patients were included in this prospective comparative study. Patients were divided into 3 groups: the first included 21 eyes of normal subjects (control group); the second included 21 eyes with PK; the third included 21 eyes with DALK. ORA was performed 2 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…4 The latest development in posterior lamellar keratoplasty is Descemet membrane endothelial keratoplasty (DMEK), a surgical procedure in which only an isolated donor Descemet membrane and its endothelial layer are transplanted. 7,8 In addition, patients commonly mention a distinct improvement of color perception after DMEK surgery, suggesting reduced color vision in FED-affected eyes. 6 Standard full contrast visual acuity may often be the key to decide the surgical treatment in patients with FED.…”
mentioning
confidence: 99%
“…4 The latest development in posterior lamellar keratoplasty is Descemet membrane endothelial keratoplasty (DMEK), a surgical procedure in which only an isolated donor Descemet membrane and its endothelial layer are transplanted. 7,8 In addition, patients commonly mention a distinct improvement of color perception after DMEK surgery, suggesting reduced color vision in FED-affected eyes. 6 Standard full contrast visual acuity may often be the key to decide the surgical treatment in patients with FED.…”
mentioning
confidence: 99%
“…Previously, studies have utilized the ocular response analyser (ORA) to investigate corneal biomechanical differences following keratoplasty. Yeneral et al and Hosny et al revealed a lower corneal hysteresis (CH) and corneal resistance factor (CRF) for PKP‐treated corneas, compared to healthy corneas, and DALK‐treated corneas. However, Jafarinasab et al demonstrated no significant difference between PKP‐ and DALK‐treated corneas for either parameter.…”
Section: Discussionmentioning
confidence: 99%
“…6 A few studies have investigated biomechanical properties of corneas thickened by stromal edema or DSAEK. [7][8][9][10][11] To the best of our knowledge, however, no studies have characterized these metrics in pseudophakic bullous keratopathy (PBK) before and after DSAEK. The purpose of the present study was to determine the extent to which DSAEK can alter these parameters in PBK.…”
mentioning
confidence: 99%